The Effective Tax Rate And Cash Flow Effect On Stock Prices (Empirical Study Of Food And Beverage Companies Listed On The Indonesia Stock Exchange (IDX) 2020-2024) - Junaidi, Ahmad; Ranidiah, Furqonti; Khair, Ummul; Akhda, Muammar (UNIVED Press, 2026)
This study aims to determine the effect of the effective tax rate and cash flow on stock prices. The study was conducted on food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. This study used a purposive sampling method and statistical analysis, including classical assumption tests, using IBM SPSS Statistics version 22. The sample size for 21 food and beverage companies listed on the IDX was 21. Therefore, the total number of 21 companies multiplied by 5 years resulted in 105 observations. The results of this study indicate that: The effective tax rate has no effect on stock prices with a significant value of 0.318. Cash flow has an effect on stock prices with a significant value of 0.046. The effective tax rate and cash flow simultaneously influence profitability with a significance value of 0.00